Mitigating the Causes of Teenagers’ Involvements in Money Ritual and Related Activities in Ogun State, Nigeria - Soluade, Zabur Olayiwola; Abdu-Raheem, Bilqees Olayinka; Agboola, Rukayat Opeyemi; Balogun, Olukunle Olagunju; Atawodi , Ibrahim (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This study assesses the mitigating causes of teenagers’ involvements in money rituals and related activities in Ogun State. The study sets out to assess the factors responsible for the pandemic of money ritual and suggests solutions to the upsurge of money ritual related killings among teenagers. The study employed a descriptive research design. The population for this study consists of all residences in Abeokuta South and Ado-Odo/Ota local government areas of Ogun state. Participants were selected using a purposive random sampling procedure. The main instrument for this study is a self-structured questionnaire tagged: “Teenager and Money Rituals Killings Questionnaire” (TMRKQ). (R =0.82). Data collected was coded and analysed using descriptive statistics of mean and standard deviation. The results show that factors such as greediness on the part of teenagers and peer group pressure contributed to teenagers' involvement in money rituals and factors such as promotion of hard work, good values system and conducts among the youths will reduce youth tendency of engaging in money rituals. Based on the findings, it is suggested that the government should punish offenders to serve as a deterrent to others and the government should improve on intelligent gathering techniques in reducing cases of money rituals killings in the country.